2004
DOI: 10.4049/jimmunol.173.2.1043
|View full text |Cite
|
Sign up to set email alerts
|

Oral Tolerance to Nickel Requires CD4+ Invariant NKT Cells for the Infectious Spread of Tolerance and the Induction of Specific Regulatory T Cells

Abstract: Previously, oral administration of nickel to C57BL/6 wild-type (WT) mice was shown to render both their splenic T cells and APCs (i.e., T cell-depleted spleen cells) capable of transferring nickel tolerance to naive syngeneic recipients. Moreover, sequential adoptive transfer experiments revealed that on transfer of tolerogenic APCs and immunization, the naive T cells of the recipients differentiated into regulatory T (Treg) cells. Here, we demonstrate that after oral nickel treatment Jalpha18(-/-) mice, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
67
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(72 citation statements)
references
References 51 publications
(56 reference statements)
5
67
0
Order By: Relevance
“…In addition animal studies involving the induction of nickel tolerance by prolonged oral contact have shown that the key cytokine involved in the nickel tolerance is IL-10. Based on these observations production of IL-10 in response to nickel challenge has been proposed as a test for identification of nickel tolerized individuals [30,31]. The presence of a significantly higher percentage of IL-10 producing cells in the peripheral blood of patch test negative otherwise normal individuals in the present study is in agreement with the protective role of IL-10 against development of CD.…”
Section: Discussionsupporting
confidence: 87%
“…In addition animal studies involving the induction of nickel tolerance by prolonged oral contact have shown that the key cytokine involved in the nickel tolerance is IL-10. Based on these observations production of IL-10 in response to nickel challenge has been proposed as a test for identification of nickel tolerized individuals [30,31]. The presence of a significantly higher percentage of IL-10 producing cells in the peripheral blood of patch test negative otherwise normal individuals in the present study is in agreement with the protective role of IL-10 against development of CD.…”
Section: Discussionsupporting
confidence: 87%
“…In our experiment, only a total of 1M nickel induced tolerance by single oral administration, indicating that oral tolerance to nickel can be achieved at a lower concentration than suggested in earlier reports 12,15,19) . In a sensitization study using painting with picryl chloride, ear swelling was suppressed by single oral administration in skin-sensitized mice 1) .…”
Section: Discussionsupporting
confidence: 55%
“…Weaker swelling in the oral-sensitization mice may be due to the lower number of Langerhans' cells, as in the case of DNCB 13) . In previous reports, oral tolerance was successfully induced in mice by drinking water containing 9M NiSO 4 for 1 week or 10 mM NiCl 2 for 4 weeks 12,15,19) . We found that immunologic tolerance to nickel could only be induced by single oral administration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such disease acceleration could also at least be partly due to a loss in Treg numbers or function previously shown to be elicited by DCs in a NKT cell-dependent fashion (45). Indeed, a loss of iNKT cells may also contribute to the decreased levels of Tregs we previously observed in NOD.CD38 null mice (27).…”
Section: Discussionmentioning
confidence: 74%